Geochemistry of sediment core PRGL1-4 - Virgil Pasquier; Pierre Sansjofre; Marina Rabineau; Sidonie Revillon; Jennifer Houghton; David A Fike (PANGAEA, 2017)
The sulfur biogeochemical cycle plays a key role in regulating Earth extquotesingles surface redox through diverse abiotic and biological reactions that have distinctive stable isotopic fractionations. As such, variations in the sulfur isotopic composition (d34S) of sedimentary sulfate and sulfide phases over Earth history can be used to infer substantive changes to the Earth extquotesingles surface environment, including the rise of atmospheric oxygen. Such inferences assume that individual d34S records reflect temporal changes in the global sulfur cycle; this assumption may be well grounded for sulfate-bearing minerals but is less well established for pyrite-based records. Here, we investigate alternative controls on the sedimentary sulfur isotopic composition of marine pyrite by examining a 300-m drill core of Mediterranean sediments deposited over the past 500,000 y and spanning the last five glacial-interglacial periods. Because this interval is far shorter than the residence time of marine sulfate, any change in the sulfur isotopic record preserved in pyrite (d34Spyr) necessarily corresponds to local environmental changes. The stratigraphic variations (>76 per mil) in the isotopic data reported here are among the largest ever observed in pyrite, and are in phase with glacial-interglacial sea level and temperature changes. In this case, the dominant control appears to be glacial-interglacial variations in sedimentation rates. These results suggest that there exist important but previously overlooked depositional controls on sedimentary sulfur isotope records, especially associated with intervals of substantial sea level change. This work provides an important perspective on the origin of variability in such records and suggests meaningful paleoenvironmental information can be derived from pyrite d34S records.
Supplement to: Pasquier, V et al. (2017): Pyrite sulfur isotopes reveal glacial-interglacial environmental changes. Proceedings of the National Academy of Sciences, 201618245, https://doi.org/10.1073/pnas.1618245114